Evolution of technical-tactical match performance indicators according to age category in women's national football teams (World Cups 2004-2019) - Caicedo-Parada, S.; Ortega-Toro, E.; Palao, J. (Journal of Physical Education and Sport, 2025)
The aim of this study was to analyze the evolution of technical-tactical performance indicators of winning and losing teams according to age category in women's national teams (U-17, U-20, and senior). The sample consisted of 505 matches (141 senior-category matches, 210 U-20-category matches, and 154 U-17-category matches) played by 47 nations. The studied variables were ball possession, chances, shots not on goal, shots on goal, efficacy, corner kicks, goals, offsides, fouls committed, yellow cards, red cards, and second yellow cards. The values of the variables were obtained from the official match reports. The results showed that efficacy, shots, and shots on goal are the variables that discriminate the match winners. The evolution in the results of this research showed different trends for the different age groups. Chances, shots on goal and shooting efficacy were the variables that made it possible to discriminate the winning team of the match in all categories in more than 94% of the matches studied. Compared to the losing teams, the winning teams took more shots. The differences between winning and losing teams showed that efficacy, shots, and shots on goal are variables that correlate with winning the match. Among the different age groups, the results show in the U-17 category a greater creation of chances, shots on goal and goals. In the U-20 category, there was a decrease in fouls committed. In the senior category, there was a trend towards an increase in the control of the game. These results reflect a balance in ball possession, which is maintained in all categories. The evolution in the results throughout the different championships and age groups reflects a tendency towards a more balanced game with greater creation of opportunities and more effective playing actions.